Perbandingan Kemampuan Menyelesaikan Masalah Matematika Pada Peserta Didik Laki-Laki Dan Perempuan Kelas VIII A SMP Negeri 4 Mamuju - Suryadi Ishak; Irmayanti Irmayanti (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2018)
This research is a qualitative descriptive study that aims to compare the ability of male and female students to solve mathematical problems in a two-variable linear equation system. The subjects of this study were 19th grade students A VII from Mamuju Middle School as many as 19 people, then 6 students were taken, consisting of 3 men and 3 women. The results showed that students with high ability categories; (1) able to understand problems; (2) able to complete planning; (3) able to solve problems; (4) can use existing information to re-examine the answers obtained. Whereas in problem solving abilities for students with moderate categories, he is able to stage (1) be able to understand the problem, (2) be able to plan solutions and, (3) be able to solve problems still in stage (4) less able to reexamine the problem solving ability of answers to students with disadvantaged categories. (1) less able to understand problems; (2) inadequate settlement planning; (3) less able to solve problems; (4) unable to use the information available to re-examine the answers obtained. Indicates that the average score of learning outcomes is 75.26. Judging from the number of students who have not finished learning, it can be concluded that the obstacle experienced by students is the lack of students' understanding of the problem given, so that they are not able to solve the problem properly. Men read and understand the problems given at a glance and women understand the problem carefully and analyze whatever information is given correctly.